CONVERSION OF DIHYDRO-1,4-OXATHIIN-3-CARBOXAMIDE TO THE ISOMERIC DIHYDRO-1,4-OXATHIIN-2-CARBOXAMIDE - HAHN, HG; CHANG, KH; LEE, WS (ELSEVIER SCIENCE BV, 1995)
The preparation of isomeric dihydro-1,4-oxathiin (3) from the dihydro-1,4-oxathiin (1) via dichloro-1,4-oxathiane (4) is described. Chlorination of 1 followed by treatment of the resulting dichloride (4) with aqueous acetone gave dihydroxy-1,4-oxathiin (5). The solvolysis to produce intermediate chlorohydrin (11) was favored relative to elimination reaction to give exomethylene compound (8). Dehydration of 5 followed by reduction afforded alpha-hydroxy-1,3-oxathiolane (2) which is a key compound to prepare the isomeric dihydro-1,4-oxathiin (3). The reason for more facile displacement of chlorine at C-2 in comparison with that at C-3 in 4 was also discussed.